Japanese encephalitis in children from an endemic district of West Bengal, India: A hospital based observational study - Gupta, Abhishek; Laha, Sumanta; Barik, Kanai Lal (Asian Journal of Medical Sciences, 2021)
Background: Japanese encephalitis (JE) is an important cause of viral encephalitis in children in South East Asian countries including India. Aims and Objective: We have done this study in an JE endemic district of India to know the demographic profile, clinical presentation, seasonal variation, outcome and about the vaccination status of the JE cases. Materials and Methods: This observational, cross sectional study was done for a period of one year in the Pediatric department of Burdwan Medical College, West Bengal in children up to the age of 12 year, presented with acute encephalitis syndrome (AES). Demographic data, clinical presentation and JE vaccination status were recorded and confirmed JE cases were detected by either serum or CSF JE IgM antibody. Outcome of the JE cases were noted as discharge, death or leave against medical advice (LAMA). Results: We have found confirmed JE in 18 children out of total 125 AES cases (14.4%). 61.1% of them were within 6 to 12 year age, mostly from low socioeconomic status and 100% case occurred during monsoon and post monsoon period. History, was of JE vaccination were present in only 11.1% case of JE. Most common presenting symptoms were high fever (100%), convulsion (94.4%) and altered sensorium (72.2%). 77.8% JE case were discharged and 11.1% expired. Conclusion: We must consider JE whenever a child from any endemic district comes with AES and we should try to bring every child under the JE vaccination coverage in the endemic regions globally to reduce the burden of this preventable encephalitis.